A Comparative Clinical Study on Effect of Agnikarma and Siravedha in Vata Kantaka w.s.r Plantar Fasciitis (AYUSHDHARA, 2023)
Vatakantaka causes very severe pain in heal region. Vata gets aggravated and localised in Khudapradesha when person walks on unevenly or irregularly on surface. It causes difficulty to daily regular activities. It can be compared to Plantar Fasciitis as there will be stabbing (Kantaka) type of pain. Incidence is about 10% of the population, about 83% of these patients being actively working between age of 25-60 years. There is only conservative management for short term relief with certain draw backs and surgical management which increase hospital stay and high economical expenses. Acharya Sushruta described Agnikarma painful condition of Twak, Mamsa, Sira, Snayu, Asthi Sandhi. Sushruta also mentioned Siravedha of vein situated two Angulas (4cm) above the Kshipramarma in Vatakantaka. The study is aimed to compare efficacy of Agnikarma and Siravedha in Vatakantaka w.s.r plantar fasciitis. A total of 40 patients are selected and randomly divided into two groups, Group A Agnikarma in 20 patients and Group B Siravedha in 20 patients. Both group given relief in symptoms of Vatakantaka. Group A - Agnikarma (90.53%) and group – B Siravedha (88.31%) were significant in treating Vatakantaka. But Agnikarma is better effect then Siravedha in management of Vatakantaka. Both therapies can be done with less economical expenditure and minimum hospitalization.